Developing Basic English Module for Secondary Level: Task Based Language Teaching - Eka Puspa Sari; St. Hartina; Sahraini Sahraini (Faculty of Education and Teacher Training of UIN Palopo, 2024)
The purpose of this study is to provide a suitable English-language curriculum for SMP Negeri 1 Bone-Bone. The five steps of the ADDIE model—analysis, design, development, implementation, and evaluation—are used in research and development as part of the research design. It used Ellis's (2017) Task Based Approach as a model to create the module. This research uses instruments such as observation, a questionnaire and interview for need analysis, expert validation, and a questionnaire for student and teacher perception. That designed module was tested on ten students of SMP Negeri 1 Bone-Bone. Therefore, the students' perception results obtained an average score of 3.64 which shows that the English module design is suitable for SMP Negeri 1 Bone-Bone. These results are supported by the results of the student questionnaire at SMP Negeri 1 Bone-Bone which are summarized as follows: the module consists of three themes, covering student needs, attractive design and layout, various integrated activities and skills, and providing guidelines for use. With modules, students can learn independently because they are adaptive and the instructions are easy.